Treatment and Survival Patterns of Primary Adenosquamous Carcinoma of the Liver: A Retrospective Analysis - Qiheng Gou; Shengya Fu; Yuxin Xie; Mengni Zhang; Yali Shen (Frontiers in Oncology, 2021)
Background and AimsPrimary adenosquamous carcinoma (ASC) is a rare liver malignancy with very little data published so far. We describe the clinical characteristics of this tumor and analyze its survival pattern to improve the diagnosis and treatment.Materials and MethodsThis study collected data of 15 patients with primary hepatic ASC in our hospital within 10 years (from 2009 to 2018). We analyzed the clinical characteristics, imaging data, treatment, and survival of ASC in the study. Two of these cases have been reported.ResultsThe common clinical symptoms of hepatic ASC are liver pain and jaundice. Laboratory examination showed that carcinoembryonic antigen (CEA) and carbohydrate antigen 19-9 (CA19-9) increased, but Alpha-FetoProtein (AFP) did not. Primary hepatic ASC is a rare subtype of intrahepatic cholangiocarcinoma (ICC) and meets the requirements of pathological diagnosis: CK20 (-), CK7 (+), CK19 (+), and p63 (+). Of the 15 patients, 11 were treated surgically, of which 3 patients received adjuvant chemotherapy. The prognosis of ASC patients is poor with a median survival time (MST) of 6 months (range: 2 to 15). The duration of MST in surgically treated patients was longer than that of nonsurgical patients (7.0 months vs. 3.0 months). Patients that received adjuvant chemotherapy survived longer (MST: 15 months). Patients with lymph node metastasis had a worse prognosis.ConclusionPrimary hepatic ASC is a rare malignant tumor with a poor prognosis. Radical surgery may be an effective treatment for prolonging survival. Surgical treatment combined with adjuvant therapy may further improve survival.